Chronic renal failure in male and female rats - Lemos, Carla C. S.; Mandarim-de-Lacerda, Carlos A.; Dorigo, David; Coimbra, Terezila M.; Bregman, Rachel (My University, 2005)
Gender influences the progression of chronic renal failure (CRF). We studied male (M) and female (F) Wistar rats for 90 days: castrated (CMc, n=7; CFc, n=6) and non castrated controls (CM, n=9; CF, n=6); castrated (CRFMc, n=8; CRFFc, n=6) and non castrated animals submitted to 5/6 nephrectomy (CRFM, n=13; CRFF, n=6). Data are expressed as mean ± SEM. Proteinuria (PTN) was higher in CRFM (554 ± 69mg/24h) compared to CRFMc (277 ± 85 mg/24h), but not in females (CRFF=193 ± 20mg/24h, CRFFc=164 ± 71mg/24h). Mesangial fractional volume increased in all CRF animals. CRF animals showed an increase of glomerular sclerosis index (GSI) and tubulointerstitial damage (TID) but in a smaller proportion in male castrated animals; the opposite occurred with females: castration induced an increase of these parameters. CRF animals showed increased cortical and glomerular fibronectin (FN) rates. Castration decreased glomerular and cortical FN rates in CRFM but not in females. In conclusion, proteinuria was higher in CRFM and probably led to glomerular and interstitial damage, as well as to FN accumulation, castration seems to protect against development of PTN, TID and FN accumulation in males. Castrated female rats presented mesangial expansion, with no changes in PTN, TID and FN rates. It seems that female sex hormones do not protect against renal disease progression, instead, we suggest that male sex hormones lead to acceleration of CRF.
Keywords: Castration; Chronic renal failure; Extra-cellular matrix; Fibronectin; Gender; Mesangium; fibronectin; sex hormone; animal experiment; animal model; animal tissue; castration; chronic kidney failure; controlled study; disease course; female; glomerulosclerosis; kidney cortex; kidney injury; male; mesangium; nephrectomy; nonhuman; proteinuria; rat; rat strain; renal protection; sex difference; Animals; Biopsy; Disease Models, Animal; Disease Progression; Female; Fibronectins; Immunoenzyme Techniques; Kidney Failure, Chronic; Kidney Glomerulus; Male; Proteinuria; Rats; Rats, Wistar; Sex Factors